2005
DOI: 10.1063/1.2135204
|View full text |Cite
|
Sign up to set email alerts
|

Carrier transport and recombination in p-doped and intrinsic 1.3μm InAs∕GaAs quantum-dot lasers

Abstract: The radiative and nonradiative components of the threshold current in 1.3 m, p-doped and undoped quantum-dot semiconductor lasers were studied between 20 and 370 K. The complex behavior can be explained by simply assuming that the radiative recombination and nonradiative Auger recombination rates are strongly modified by thermal redistribution of carriers between the dots. The large differences between the devices arise due to the trapped holes in the p-doped devices. These both greatly increase Auger recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
84
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 9 publications
7
84
0
Order By: Relevance
“…It has previously been suggested that the form of the carrier distribution changes around room temperature in the p-doped structures 4,11 and this may be the origin of the change in the gain that we observe. We examine this in Fig.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…It has previously been suggested that the form of the carrier distribution changes around room temperature in the p-doped structures 4,11 and this may be the origin of the change in the gain that we observe. We examine this in Fig.…”
supporting
confidence: 56%
“…͓DOI: 10.1063/1.2361167͔ p-type modulation doped In͑Ga͒As quantum dot lasers have attracted much interest recently, partially due to reports of an infinite or negative characteristic temperature ͑T 0 ͒ around room temperature. [1][2][3] Several authors have attributed this behavior to the temperature dependence of the Auger recombination process in doped structures, 2,4,5 although the particulars of the explanation varied in each case. In this work we report on measurements made on both intrinsic and p-doped quantum dot structures that emit at 1.3 m. From studying the radiative and nonradiative components of the threshold current we show that the temperature performance of p-doped lasers can be described without needing to consider Auger recombination.…”
mentioning
confidence: 99%
“…4 The lasing wavelength of the devices was approximately 1.28 m at room temperature. The active region consisted of ten stacked InAs dot-ina-well layers separated by either modulation p-doped or intrinsic GaAs barriers sandwiched by GaAs waveguide and AlGaAs cladding layers.…”
mentioning
confidence: 98%
“…5,6 Recent results reported that the superior thermal stability of InAs/ GaAs p-doped QD lasers around room temperature arises from a combination of improving thermal distribution of the electrons, leading to a decrease in the radiative current necessary to reach the lasing threshold, and an increase in nonradiative Auger recombination with temperature, together giving rise to a constant threshold current over a limited temperature range. 4 In this work, we consider the temperature sensitivity of the gain and specifically, the effect of the nonthermal distribution of the carriers on the gain characteristics of p-doped devices and compare the results to those obtained with intrinsic quantum dot lasers.The gain was measured using the method described by Hakki and Paoli 9 at both room temperature, where carriers in the intrinsic devices are in thermal equilibrium, and at 350 K, where carriers in the p-doped lasers are expected to be closer to thermal equilibrium. 4 The lasing wavelength of the devices was approximately 1.28 m at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation